Management of Massive Hemorrhage after Percutaneous Nephrolithotomy: Angioembolization or Renorrhaphy - Murat Tuncer (Journal of Urological Surgery, 2015)
Objective We present two treatment modalities, selective renal angioembolization and renorraphy, in massive renal hemorrage after percutaneous nephrolithotomy (PCNL) that could not be controlled by conservative methods. Materials and Methods One thousand two-hundred patients, who had undergone PCNL between January 2003 and February 2014, were retrospectively reviewed. From these cases, we selected patients with massive post procedural bleeding that could not be taken under control by conservative methods and we reviewed their clinical course and treatment results. Results Bleeding could not controlled by conservative methods in 6 patients and, angioembolization was done succesfully. In 3 patients, angioembolization was not available. Renorraphy was performed in 2 patients and nephrectomy in 1 patient at first attempt. Renorraphy could not solve the problem of massive hemorrage and these 2 patients eventually underwent nephrectomy. Conclusion Renal angiography and embolization is an effective and safe method and renorraphy should not be the first option in massive bleeding after PCNL that can not be taken under control by conservative methods.